Theoretical study on the redox reaction mechanism of quinone compounds in industrial processes. (18th May 2019) - Tarumi, Moto; Matsuzaki, Yoichi; Suzuki, Kimihito
Graphical abstract: Highlights: Quinone compounds work as catalysts in the desulfurization process called the Takahax process. Density functional theory calculations identified rate-determining steps in the process. Rate-determining steps have been characterized as proton-coupled electron transfer reactions. Abstract: Density functional theory calculations have been performed to understand the reaction mechanisms of the industrial desulfurization process, also called the Takahax process, which is used in Japanese steelworks to remove hydrogen sulfide (H2 S) from coke oven gas. In this process, H2 S is oxidized by 1, 4-naphthoquinone-2-sulfonic acid (NQS), which is itself reduced to 1, 4-dihydroxynaphthalene-2-sulfonic acid (NQSH2 ). NQS can be regarded as a catalyst. On the basis of our calculations, we have revealed that the rate-determining steps in the catalytic reactions can be characterized as proton-coupled electron transfer (PCET) that is governed by the frontier molecular orbitals of catalysts. Furthermore, energetic considerations show that the sequential electron and proton transfer mechanism may comparably contribute to the concerted mechanism depending on the magnitude of the electrostatic interaction between the electron donor and acceptor that stabilizes the TS of the concerted PCET.